Pelatihan Budidaya Tanaman Aren Untuk Meningkatkan Kapasitas Masyarakat Desa Lubuk Ogung Kecamatan Bandar Sei Kijang Kabupaten Pelalawan Provinsi Riau - Yeni Kusumawaty; Roza Yulida; Tengku Harunur Rasyid; Armaini Armaini; Evy Maharani; Susy Edwina; Rahmayuni Rahmayuni (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
In Riau Province, the majority of community farming is oil palm gardening. But at present, the market mechanism causes the price of palm oil purchased from the population to be very low. In the Village of Kiyap Jaya, Bandar Sei Kijang District, planting of palm trees has begun in between the oil palm plants which were pioneered by one of the oil palm farmers. The location is in Lubuk Ogung Village, which is adjacent to Kiyap Jaya Village and has not yet cultivated sugar palm plants to develop sugar palm centers in Lubuk Ogung Village. The target communities of village development activities are villagers including small-scale oil palm farmers who own oil palm or yard plots. Community service activities consist of contacting village officials and material preparation; preparation of Human Resources (farmers) with the formation of four groups of sugar palm farmers; land allocation; theoretical training and technical practice of seedling and cultivation of palm trees and nursery and hatchery activities and planting of palm seeds in the prepared land location. The benefit of the activity is that the farmer understands the economic prospects of sugar palm products that are very high so that they have the motivation to pursue sugar palm seedlings and planting; farmers have the ability to breed and cultivate sugar palm plants, and the farmers carry out the practice of seed seeding in groups to become high quality and economically valuable palm saplings. The implementation of the activity was considered successful.